Carinal transplantation. Issue 11 (November 1992) - Ueda, H; Shirakusa, T
Abstract : BACKGROUND: Current techniques of management of carinal lesions are not always satisfactory. Carinal transplantation, if feasible, would be valuable in certain circumstances. METHODS AND RESULTS: Carinal transplantation experiments were performed in dogs. In early cross transplant experiments there were problems in controlling ventilation and in obtaining satisfactory anastomoses, and the animals failed to live for even a few days. In seven subsequent experiments the carinal graft was removed from one dog and transplanted into a second dog. Two dogs lived for over four months with immunosuppression. CONCLUSION: The results suggest that carinal transplantation can succeed if (1) the calibre of the graft is matched with that of the recipient; (2) there is an abundant blood supply to the graft; (3) appropriate immunosuppression is provided; (4) ventilation is adequate during surgery.